A direct comparison of voice pitch processing in acoustic and electric hearing - Steinmetzger, Kurt; Meinhardt, Bastian; Praetorius, Mark; Andermann, Martin; Rupp, André (NeuroImage: Clinical, 2022)
In single-sided deafness patients fitted with a cochlear implant (CI) in the affected ear and preserved normal hearing in the other ear, acoustic and electric hearing can be directly compared without the need for an external control group. Although poor pitch perception is a crucial limitation when listening through CIs, it remains unclear how exactly the cortical processing of pitch information differs between acoustic and electric hearing. Hence, we separately presented both ears of 20 of these patients with vowel sequences in which the pitch contours were either repetitive or variable, while simultaneously recording functional near-infrared spectroscopy (fNIRS) and EEG data. Overall, the results showed smaller and delayed auditory cortex activity in electric hearing, particularly for the P2 event-related potential component, which appears to reflect the processing of voice pitch information. Both the fNIRS data and EEG source reconstructions furthermore showed that vowel sequences with variable pitch contours evoked additional activity in posterior right auditory cortex in electric but not acoustic hearing. This surprising discrepancy demonstrates, firstly, that the acoustic detail transmitted by CIs is sufficient to distinguish between speech sounds that only vary regarding their pitch information. Secondly, the absence of a condition difference when stimulating the normal-hearing ears suggests a saturation of cortical activity levels following unilateral deafness. Taken together, these results provide strong evidence in favour of using CIs in this patient group.
Online veröffentlicht am 10. September 2022, Artikelversion 13. September 2022
Gesehen am 17.10.2022